Tracheoesophageal fistula managed with tracheal stent through flexible bronchoscopy without fluoroscopy - G. Stratakos; C. Zisis; I. Bellenis; V. Filaditaki; A. Liapikou; S. Zakynthinos; C. Roussos (Monaldi Archives for Chest Disease, 2016)
Inoperable malignant tracheoesophageal fistula (TEF) is characterised by an extremely poor prognosis. Tracheal or double (tracheal-esophageal) stenting through rigid bronchoscopy has been suggested as a valuable therapeutic option. We report on a patient with a large TEF successfully sealed by deployment of a self-expandable stent through flexible bronchoscopy (FB) without fluoroscopy. Dramatically improved health status permitted him to undergo radiation, attaining further clinical improvement. Four months after stent placement no sequelae were observed. During the fifth month a new fistula developed distally to the stent finally leading to death from septic complication. Palliative management of inoperable malignant TEF by tracheal stent placement through FB without fluoroscopy, is feasible, safe and rewarding leading to important clinical improvement.